PENGOLAHAN TEKNIK SURFACE TEXTILE DESIGN DENGAN INSPIRASI STRUKTUR HIV PADA BUSANA DEMI COUTURE - Alvin Mei Triyas Wahyuni; Aldi Hendrawan (Jurusan Seni Rupa ISBI Bandung, 2018)
AIDS (Acquired Immunodeficiency Syndrome) is a syndrome or collection of symptoms formed by retroviruses. HIV/ AIDS is part of the compiler called the structure or morphology of HIV. Each component if observed using a microscope forms a circle shape. Among the bad views on people with HIV, the authors see the aesthetic potential in the HIV structure. The HIV’s elements contained balance, unity, rhythm, and proportion which has an aesthetic potential to be developed into textile products. The author raised the phenomenon as a design idea in developing and becoming one of the inspirational motives found in the morphology or structure of HIV. The structure will be processed using surface textile design techniques by using digital printing, heat settings (steam), puff paint, beading, stitching and patchwork collages that composed for fashion products called demi couture.Keywords: HIV, Psychology of HIV, HIV Structure, Surface Textile Design Technique, Demi Couture _______________________________________________________________ Penyakit AIDS (Acquired Immunodeficiency Syndrome) adalah sindrom atau kumpulan gejala yang dibentuk oleh retrovirus. HIV/ AIDS adalah bagian dari penyusun yang disebut dengan struktur atau morfologi HIV. Setiap komponen jika di terjemahan menggunakan mikroskop yang membentuk struktur tersebut adalah bentuk lingkaran. Diantara pandangan buruk pada penderita ODHA, penulis melihat adanya potensi estetika pada struktur HIV. Dia memiliki unsur keseimbangan, kesatuan, ritme, dan proporsi untuk dikembangkan menjadi produk tekstil. Penulis mengangkat fenomena tersebut sebagai ide desain dalam mengembangkan dan menjadi salah satu inspirasi motif yang terdapat pada morfologi HIV. Struktur tersebut akan diolah dengan menggunakan teknik surface textile design dengan teknik digital printing, heat setting (steam), puff paint, beading, dan stitching yang dikomposisikan untuk produk busana yang disebut demi couture.Kata Kunci: HIV, Psikologi HIV, Struktur HIV, Teknik Surface Textile Design, Demi Couture